Perancangan Desain Interaksi Modul Informasi Objek Pelayanan Publik Pada Aplikasi Malang Service Dengan Menggunakan Metode HCD (Human Centered Design) - Dhimas Ilmi Auvi; Herman Tolle; Hanifah Muslimah Az-zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Public service can be interpreted as a form of service, either in the form of public goods and public services, which in principle be the responsibility of and implemented by Government agencies, Central, Regional, and in Badan Usaha Milik Negara (BUMN) or Badan Usaha Milik Daerah (BUMD). According to Mayor of malang in the year 2019 says that in the system of government of Malang City to Smart City Services declared left far behind if compared with the other city whose already implementing the smart city. Based on the statement that Malang has not implemented optimally of smart city services where the use of such services can facilitate the wider community to get information and services through technological devices. At this time, in various big cities in Indonesia has been contribute in the implementation of the empowerment of the Smart City where the era of technologically as the current technology exist side by side with human life that can help day to day activities.Based on the results of the analysis can be taken a positive side as a step to delivery of public services to the community, where that community can be more easy and practical when people want to get public administration or service such as management letters and other important information, so in the manifest can be done by using a smartphone app or mobile apps for service information public of Malang City that can be accessed without limitations of place and time of the user. In the design interactive design mobile apps which are oriented to user and stakeholders can use the Methods of HCD (Human-Centered Design) with four stages that analyze the context of the user, determine user needs, create design solutions, and evaluation of design solutions. At the evaluation stage, testing was carried out with 15 respondents who had adjusted their characteristics and obtained an effectiveness aspect of 93%, and efficiency aspect of 92.21%, and a satisfaction aspect using the SUS (System Usability Scale) questionnaire of 79.67.